'To unlock the secret places of Man's Mind'.1 Thomas Willis (1621–1675). (August 2022) - Hunting, Penelope
Thomas Willis was born four hundred years ago on 27 January 1621 in Wiltshire. He has been dubbed 'the father of neurology' and is remembered for the Circle of Willis at the base of the brain. Young Thomas was educated at Oxford as a schoolboy and undergraduate. From 1646 he practised medicine and studied chemistry; he joined the Oxford Experimental Philosophical Club, and was Sedleian Professor of Natural Philosophy from 1660. He established a prosperous medical practice at The Angel on Oxford High Street, and achieved international acclaim for Cerebri anatome (1664). Lured to London in 1667, Willis lived in style but attended the sick poor on Sundays and worshipped twice daily at St Martin-in-the-Fields.